Implementation of Throw-and-Catch Ball Games to Improve Gross Motor Skills and Socio-Emotional Development of Children at TK ABA 30 - Ma’fira, Yulliza (Yayasan Rahmat Islamiyah, 2026)
This study aims to implement throw-and-catch ball games as an effort to improve the gross motor skills and socio-emotional development of children at TK ABA 30. The problem addressed is the low level of basic motor movement skills and children’s social interaction during learning activities. The research method used was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. The research subjects were 20 children of Group B at TK ABA 30. Data were collected through observation and documentation, while data analysis was carried out using descriptive quantitative and qualitative techniques. The results of the study show that the implementation of throw-and-catch ball games significantly improved children’s gross motor and socio-emotional skills in each cycle. Thus, the throw-and-catch ball game is proven to be an effective learning strategy to optimize early childhood development.